Comparison of Totally Extraperitoneal versus Transabdominal Preperitoneal repair of inguinal hernias - Yadav, Rohit Prasad; Gautam, Manish; Koirala, Ashok; Bhattarai, Sameer; Shah, Sachhidanand; Giri, Pankaj (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Laparoscopic inguinal hernia repair is a tension-free mesh repair that is based on pre-peritoneal approach of repair. It provides mechanical advantage to the surgeon, by being able to place a large piece of mesh and by using the natural force of the abdominal wall to disperse the intra-abdominal pressure over a large area to support the mesh. This retrospective study is aimed to study the demography of inguinal hernia and to compare operating time, complications and postoperative pain between patients undergoing Total Extrapritoneal (TEP) or Transabdominal Preperitoneal (TAPP) repair. Methods: A retrospective comparative study was conducted in patients with inguinal hernia who underwent laparoscopic repair by either TEP or TAPP, between April 2019 to July 2020 at Nobel Medical Collage Teaching Hospital, Biratnagar, Morang. Age, sex, type of hernia, duration of operation, post-operative complications, severity of pain and duration hospital stay were analyzed between two groups of patients undergoing surgery by either TEP or TAPP. Results: One hundred and five patients underwent either TEP or TAPP during study period. There were 96 males and 9 females. There were 50 patients with right, 40 with left and 6 patients with bilateral inguinal hernia. Four patients had left sided irreducible inguinal hernia, 2 patients had bilateral recurrent inguinal hernia, 2 patients had right sided recurrent inguinal hernia and 1 patient had left sided recurrent inguinal hernia. There was significant difference in duration of operation (TEP 64.43min) / (TAPP 84.46min), p<0. 001. Total duration of hospital stay and postoperative pain were not significant between patients operated with TEP or TAPP. Accidental pneumoperitoneum was noticed in 8 cases, 10 cases of subcutaneous emphysema, 5 cases of seroma and 1 case of scrotal hematoma in TEP group. In TAPP group scrotal hematoma occurred in 4 cases and seroma in 5 cases which was not significantly different from TEP group. Conclusion: TAPP had significantly longer operating time as compared to TEP. However, there was no significant difference in post-operative pain and hospital stay in both group.